MENINGKATKAN MOTIVASI BELAJAR IPS MELALUI MODEL NHT PADA SISWA KELAS 7A SMPN 1 HARUAI (PENELITIAN TINDAKAN KELAS PADA SISWA KELAS 7A SMPN 1 HARUAI) - Norpah Norpah (JURNAL SOCIUS, 2015)
This study was a classroom action research. This study aims to improve the students’ learning motivation through the cooperative learning method, especially the numbered heads together model, which is relevant to the situation and condition in year VII A SMP Negeri 1 Haruai.  The learning motivation will impact to learning achievement.  The study consisted of two cycles.  The data were collected through observations, tests, quesioners, and documents.  The data were analyzed by the qualitative descriptive technique.  The result of the study show that during the action implementation, the students’ learning motivation were improved.  Therefore, the application of the model to improve the students’ social science learning motivation.Key words: learning motivation, numbered heads together model.